Exploring the effect of the clothes used in physical education class on some physical fitness parameters - Mehmet Yahya Tatari; Nalan Suna; Mert Kurnaz (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Clothing used in physical education class can affect physical fitness. Therefore, the aim of this study was to explore the effect of clothes used in physical education class on some physical fitness parameters (anthropometric characteristics, muscular endurance, flexibility, explosive strength). 34 secondary school student were recruited for this study. After the baseline assessments, the students were randomly divided into two groups: one group wearing shorts and T-shirts and the other wearing school uniforms. The analysis revealed baseline differences in the sit-and-reach, standing long jump, sit-up and 20 m sprint tests in within-group comparisons. Girls performed better when wearing shorts and T-shirt in the 20 m sprint test (Z(-3.622)=4.45, p<0.01), sit-and-reach test (Z(-3.668)=27.41, p=0.01), SLJ (Z(-3.635)=124.02, p=0.01) and sit-up test (Z(-3.534)=18.82, p<0.01). Similarly, boys performed better when wearing shorts and T-shirt in the 20 m sprint test (Z(-3.574)=4.68, p<0.01), sit-and-reach test (Z(-3.657)=24.64, p=0.01), SLJ (Z(-3.667)=141.14, p=0.01) and sit-up test (Z(-3.537)=22.91, p<0.01). In conclusion, the results revealed that wearing shorts and T-shirts in physical education class had a positive effect on some physical fitness parameters. This underlines the advantages of wearing appropriate clothing in physical education class to promote physical fitness.